Development of learning animation media to improve students' mathematical understanding - Ulpah, Maria; Insani, Arfita Ade Nur (Program Studi Pendidikan Matematika, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mulawarman, 2025)
Mathematical comprehension ability is essential for students to achieve proficiency in mastering mathematical material. Innovation is needed, such as using animated learning media that can display illustrations visually to increase student interest. The purpose of this study was to develop valid and effective animated video learning media to improve the mathematical comprehension ability of grade VIII students. The method used was the Research and Development with the Bergman & Moore model. The instruments were questionnaires and tests. The study results showed that the learning animation video was valid and interesting with a percentage of validation by material experts of 81,3% (valid of a good predicate) and media experts of 89% (valid of a good predicate). The learning animation video effectively improved students' mathematical understanding abilities with an average class N-Gain score of 0,58 (moderate).